The process of alcoholization among the indian population of the Upper Rio Negro river and CAGE's limitations as a screening instrument for alcohol dependence (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Through a qualitative and interdisciplinary investigation as to the theoretical validity of CAGE as a screening instrument for alcohol dependence among the Upper Rio Negro Indian population, the use of alcohol as a theme among culturally diverse groups is approached by studying the assignment of meanings to drinking and the answers given to CAGE by the interviewed Indians. METHODS: Geertz (1989) and Menendez's (1982) contributions have allowed the distinction between the biomedical concept of alcohol dependence and the social notion by the drinkers. Both notions were submitted to the alcoholization process concept which refers back to the ambiguous and conflicting relationships established between drinkers and non-drinkers in historical moments and specific social situations. RESULTS: The analysis of the answers to CAGE made evident the incongruence between its objectives and assumptions and the indigenous understanding of the instrument, invalidating a productive use. CONCLUSION: Despite CAGE's universalist intentions, the indigenous cultural singularity produced new and unexpected meanings to the test-questions and generated useless answers to carry out the screening of suspects of alcohol dependence, in the studied situation.